Space and Innovations in the Context of Space Law - O. A. Volynskaya (Московский журнал международного права, 2012)
Now, after fifty years of space exploration, the world is facing a new challenge – transition from scientific research to practical use of space for the benefit of humanity. To ensure transfer of perspective space technologies to the Earth economy space-faring nations are developing comprehensive regulatory frameworks for innovation-based development to ensure strong positions of national enterprises in world space markets.This article covers international law aspects and specific features of US and European space legislations on innovations. Legal mechanisms and strategies successfully applied in these regions can be a starting point for modernizing other world economies oriented to innovative development.